Obstacles to applying ABA techniques from the standpoint of autism teachers (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of the research is to identify the obstacles to the application of ABA techniques from the point of view of autism teachers in some autism centers in Damascus, and to identify the impact of some variables such as academic qualification and the number of years of experience. The research sample included (100) male and female teachers, (61) female teachers, (39) teachers. The obstacle scale was used by the researcher. As for the study, the following results were reached: The obstacles to applying the techniques of applied behavior analysis were moderate, and the presence of statistically significant differences in The responses of the study sample individuals are due to the gender variable and in favor of the females, and there are no statistically significant differences in the answers of the study sample individuals due to the scientific qualification variable, except after the time and place constraints, and the presence of statistically significant differences in the responses of the study sample individuals due to the variable number of years of experience.
Keywords: Autism; Applied Behavior Analysis; Autism Educators